2019
DOI: 10.1038/s41598-019-53823-w
|View full text |Cite|
|
Sign up to set email alerts
|

The spatiotemporal organization of episodic memory and its disruption in a neurodevelopmental disorder

Abstract: Recent theories of episodic memory (EM) posit that the hippocampus provides a spatiotemporal framework necessary for representing events. If such theories hold true, then does the development of EM in children depend on the ability to first bind spatial and temporal information? And does this ability rely, at least in part, on normal hippocampal function? We investigated the development of EM in children 2–8 years of age (Study 1) and its impairment in Williams Syndrome, a genetic neurodevelopmental disorder c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…The HPC is involved in cognitive functions, including learning and memory ( O’Keefe, 1993 ; Bird and Burgess, 2008 ; Aronov et al, 2017 ; Korotkova et al, 2018 ; Mastrogiuseppe et al, 2019 ). Theta oscillations in the septo-hippocampal axis are thought to support learning and memory because disruption of the theta oscillations by MS inactivation impairs HPC-dependent memory as well ( Mizumori et al, 1990 ; Bannerman et al, 2004 ; Lecourtier et al, 2011 ; Wang et al, 2015 ).…”
Section: Roles Of the Ms In Physiological Oscillationsmentioning
confidence: 99%
“…The HPC is involved in cognitive functions, including learning and memory ( O’Keefe, 1993 ; Bird and Burgess, 2008 ; Aronov et al, 2017 ; Korotkova et al, 2018 ; Mastrogiuseppe et al, 2019 ). Theta oscillations in the septo-hippocampal axis are thought to support learning and memory because disruption of the theta oscillations by MS inactivation impairs HPC-dependent memory as well ( Mizumori et al, 1990 ; Bannerman et al, 2004 ; Lecourtier et al, 2011 ; Wang et al, 2015 ).…”
Section: Roles Of the Ms In Physiological Oscillationsmentioning
confidence: 99%
“…In order for our sample to be representative of ASD individuals, participants with and without ASD were selected from late childhood to young adulthood, given the very moderate or even absent effect of age on this period in TD population, and the absence of age influence in memory difficulties in ASD [Desaunay et al, 2020]. Developmental studies show that memory for associations emerges early in TD population, with a pronounced increase until the age of 10, followed by a period of relative stability until adulthood [Guillery‐Girard et al, 2013; Mastrogiuseppe, Bertelsen, Bedeschi, & Lee, 2019], with similar visual associative memory performance between late childhood and adulthood [Baadte & Meinhardt‐Injac, 2019]. Congruent with these age‐related differences, EEG studies have identified a greater reliance on recollection‐based recognition during early childhood, shifting more toward a familiarity‐based recognition from late childhood to adulthood [see Friedman, 2013; Friedman, de Chastelaine, Nessler, & Malcolm, 2010, for a review].…”
Section: Introductionmentioning
confidence: 99%
“…This might indicate that the spatial component of EM might be improved through the compensatory engagement of unaffected areas of the brain such as the network of cortical areas involved in visual scene processing [19]. In contrast, the temporal binding of memory components, which has been shown to require an intact hippocampus [11] 7/9 https://doi.org/10.12786/bn.2020.13.e15…”
Section: Discussionmentioning
confidence: 99%
“…The AD group received a total of 16 training sessions between the pre-test and post-test, which was conducted 2 days a week for 8 weeks. During the sessions, the AD group performed an active behavioral task of EM that required the binding of “what”, “where”, and “when” information [ 11 ] with feedback on each trial. Standard neuropsychological assessments were also implemented before and after the training in random order by a non-blinded occupational therapist.…”
Section: Methodsmentioning
confidence: 99%